MULTIFACETED PUBLICIST T. SYDYKBEKOVA (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
The article analyzes the thematic variety of publicist T. Sydykbekova
Keywords: publicism, publicist, topic and idea, diversity.